2011
DOI: 10.1111/j.1365-2796.2010.02327.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior pituitary axis hormones and outcome in acute ischaemic stroke

Abstract: .  Neidert S, Katan M, Schuetz P, Fluri F, Ernst A, Bingisser R, Kappos L, Engelter ST, Steck A, Müller B, Christ‐Crain M (University Hospital Basel, Basel, Switzerland; SphingoTec GmbH, Borgsorf, Germany; Kantonsspital Aarau, Aarau, Switzerland) Anterior pituitary axis hormones and outcome in acute ischaemic stroke. J Intern Med 2011; 269: 420–432. Background.  Early and accurate prediction of outcome in acute stroke is important and influences risk‐optimized therapeutic strategies. Endocrine alterations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 40 publications
4
66
1
1
Order By: Relevance
“…Ziet al, in a cohort study, observed that cortisol level is related to 90-day mortality rate [5] Markund et al, in a study on 88 patients with cerebral infarctions, observed that high level of cortisol is related to delirium and mortality [7]. Similar studies in Switzerland, America and Denmark also confirmed above findings [6,8,20]. Some researches show that cortisol level change is seen only in stroke, but not in TIA [21].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Ziet al, in a cohort study, observed that cortisol level is related to 90-day mortality rate [5] Markund et al, in a study on 88 patients with cerebral infarctions, observed that high level of cortisol is related to delirium and mortality [7]. Similar studies in Switzerland, America and Denmark also confirmed above findings [6,8,20]. Some researches show that cortisol level change is seen only in stroke, but not in TIA [21].…”
Section: Discussionsupporting
confidence: 69%
“…Change in serum level of this hormone have been reported in patients with ischemic stroke and some studies suggested high levels of this hormone is independently associated with increase in ischemic lesion volume [5]. Also, some studies indicated that cortisol level in patients with ischemic stroke is associated with significantly increased mortality rate [4,6,7]. Some studies reported a Correlation between cortisol level and post stroke physical and psychological disability [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These included CRP [7][8][9], IL-6 [2], matrix metalloproteinase-9 [10], fibrinogen [11], brain atriuretic peptide [12], and cortisol [13]. How- Cryptogenic (IV) 12.0 ± 6.0 Hypothalamic…”
Section: Discussionmentioning
confidence: 99%
“…All three included studies measured the outcome at three months [32,44,45]. Low cortisol levels are possibly linked to a good outcome at three months.…”
Section: Discussionmentioning
confidence: 99%